2008
DOI: 10.3758/mc.36.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative interactions of model- and experiencebased processes: Implications for type and flexibility of representation

Abstract: People are often taught using a combination of instruction and practice. In prior research, we have distinguished between model-based knowledge (i.e., acquired from explicit instruction) and experience-based knowledge (i.e., acquired from practice), and have argued that the issue of how these types of knowledge (and associated learning processes) interact has been largely neglected. Two experiments explore this issue using a dynamic control task. Results demonstrate the utility of providing model-based knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…Our findings are more consistent with a view that emphasizes the interaction between such knowledge (e.g., Klein, 1998;Koriat et al, 2008;Lane et al, 2008;Mathews et al, 1989;Sallas et al, 2007). Specifically, participants in our experiments appeared to use automatically acquired knowledge (i.e., the perception of overall effectiveness) to explicitly estimate the effects of interventions.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our findings are more consistent with a view that emphasizes the interaction between such knowledge (e.g., Klein, 1998;Koriat et al, 2008;Lane et al, 2008;Mathews et al, 1989;Sallas et al, 2007). Specifically, participants in our experiments appeared to use automatically acquired knowledge (i.e., the perception of overall effectiveness) to explicitly estimate the effects of interventions.…”
Section: Discussionsupporting
confidence: 80%
“…This direct impact of experience-based knowledge on explicit representations of the effects is a type of interaction between the two types of knowledge different from those found in past research. In past research, we have found that providing just-in-time explicit knowledge can enhance experience-based learning (Lane et al, 2008;Sallas et al, 2007). We also have found that automatically acquired knowledge of an artificial grammar slowly becomes accessible to conscious awareness over time and can be used to correctly verbalize syntactical components of a grammar after extensive training .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, research has demonstrated that participants can sometimes learn and perform tasks correctly with little explicit knowledge of the features they are relying upon (e.g. Reber, 1993;Lane, Mathews, Sallas, Prattini, & Sun, 2008; for a general introduction, see Gladwell, 2005). Similarly, others have argued that people's explanations of how they make decisions bears little resemblance to the actual process of decisionmaking (e.g.…”
mentioning
confidence: 99%